Sistem Telemetri Nirkabel Menggunakan Long Range (LoRa) untuk Deteksi Dini Kebakaran Hutan - Azwar, Hamid; Muhammmad Diono; Rizadi Sasmita Darwis (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
Wireless telemetry has the advantage of increasing productivity in accessing measurement data information in real time even when the user is not at the measurement location. Various types of methods are used to implement the telemetry system. One of the methods used is sending measurement data using Long Range (LoRa). LoRa has a small power consumption and can transmit data over a longer distance compared to Wifi technology. In this research, a prototype telemetry system will be built to transmit forest fire detection sensor data using LoRa communication. The system consists of 2 nodes where the maximum delivery reach reaches 700 meters for each node and the delivery delay reaches 23.22 seconds. The temperature and humidity sensor data have an accuracy of 4% and 8%, respectively. Sending sensor data can be displayed using Blynk. Keywords: LoRa, Telemetri, gateway, internet, sensor